The national between the global and the local: Commemorating the First World War in Germany (Comillas Journal of International Relations, 2015)
Some German commentators have spoken of 2014 as the Supergedenksjahr –the super commemoration year– which marks the 25th anniversary of the fall of the Berlin Wall, the 75th anniversary of the start of the Second World War, and the centenary of the outbreak of the First World War. This article offers a number of observations about the commemoration of the First World War within the context of a broader politics of history in contemporary Germany. First, the First World War has emerged from the shadows of the two other major events in twentieth-century German history – the Third Reich and the division of Germany overcome in 1989. Whether this will remain the case is doubtful, as the pull of the other events remains stronger. Second, if there was a single overriding debate in Germany about the First World War it owed much to the success of The Sleepwalkers by Christopher Clark. His thesis of shared responsibility was read against the background of Fritz Fischer’s thesis, which ascribed most responsibility to reckless German leaders. In turn, the re-emergence of the war guilt debate was related to discussions about Germany’s role in European politics today. Finally, the commemoration has been marked by a move away from the nation-state framework so that many exhibitions and programmes adopt either a global or a local perspective.
Keywords: Super Commemoration Year; global; Third Reich; Berlin Wall; Sleepwalkers